CatWalk gait analysis in a rat model of multiple sclerosis. Issue 1 (December 2016) - Herold, Sabine; Kumar, Prateek; Jung, Klaus; Graf, Irina; Menkhoff, Henrike; Schulz, Xenia; Bähr, Mathias; Hein, Katharina
Abstract Background Myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE) is a widely used animal model for multiple sclerosis. The characteristic feature of the MOG-EAE model in Brown Norway rats is consistent involvement of the spinal cord resulting in limb paresis. The aim of the study was to investigate whether early subclinical gait abnormalities are present in this animal model and can be detected by CatWalk XT, a fully automated gait analysis system. Furthermore, we investigated the usability of CatWalk system for treatment studies. Results Our gait analysis showed no preclinical abnormalities in MOG-EAE animals. Nevertheless, we characterized a combination of gait parameters that display a high predictive capacity in regard to disease onset. Our detailed histopathological analysis of the spinal cord revealed that lesion formation starts in the lumbar region and propagates toward the cervical part of the spinal cord during the disease course. In the treatment study, the stabilization of gait parameters under the treatment with methylprednisolone was detected in CatWalk as well as in traditional EAE-scoring system. Conclusions The results from CatWalk test indicate no benefit of lab-intensive automated gait system in EAE-model with chronic-progressive disease course as well as in therapeutic studies with pronounced effect on the severity of clinical symptoms. However, due to its quantitative and objective nature this system may display a refined test to detect small but functional relevant changes in regeneration-orientated studies.